Forecasting ultra‐short‐term wind power by multiview gated recurrent unit neural network. Issue 10 (29th July 2022) - Xiong, Bangru; Fu, Mengqin; Cai, Qiuting; Li, Xiaoyan; Lou, Lu; Ma, Hui; Meng, Xinyu; Wang, Zhengxia
Abstract: Wind power generation prediction plays an important role in the safety and economic operation of the power system. There are many parameters recorded in wind farm data, such as wind power, wind speed, wind direction, and so on. Traditional wind power prediction modeling methods lack the mining of these parameter data and fail to make good use of some potential physical information. To address this challenge, this paper proposes a multiview neural network learning framework to predict wind power. One is the data attribute view of wind power, which uses the historical data feature of the wind power itself to learn the future wind power feature. The other is the physical attribute view of wind power, which uses the physical attribute features associated with the wind power definition to learn the future features. Then all the learned features are jointly fused to predict the future wind power values. In addition, an uncertain factor is proposed and computed, which is inspired by the wind power formula and usually associated with internal and external environment perturbation. All time series features are input into the gated recurrent unit neural network to form a hybrid neural network framework for wind power prediction. Experimental results under the measured condition and the standard condition of wind farms demonstrate the effectiveness of the proposed method. Abstract : On the basis of the temporal and physical characteristics of wind farm data, this paper constructed a wind power prediction model with multiview data features. At the same time, the uncertainty factors of environmental disturbance and wind turbine state changes are considered and combined with the power prediction model and good results are achieved.